Enhancement of the SrTiO3 Surface Reactivity by Exposure to Electric Fields. Issue 7 (11th June 2019) - Klauke, Kurt; Kayaalp, Buğra; Biesuz, Mattia; Iannaci, Alessandro; Sglavo, Vincenzo M.; D'Arienzo, Massimiliano; Lee, Siwon; Seo, Jongsu; Jung, WooChul; Mascotto, Simone
Abstract: In the present work the effect of electric field assisted treatments, i. e. flash sintering, on the physicochemical properties and surface reactivity of SrTiO3 nanoparticles is investigated. The materials were prepared by a hydrothermal approach and consolidated at high temperatures by conventional and electric field assisted procedures. The exposure to an electric field from 300 to 900 V/cm allowed rapid consolidation with progressive reduction of the grain growth and the shrinkage of the specific surface area to 22% and 43%, respectively. XPS analyses evidenced increasing Sr segregation at the surface if voltage was applied during the treatment. The corresponding presence of Sr vacancies in the perovskite lattice was demonstrated by ESR spectroscopy. Both techniques pointed out the appearance of highly oxidative O − species in all ceramics. The materials reactivity was investigated by methane oxidation, chosen as model high temperature catalytic reaction. With respect to conventionally treated SrTiO3, the surface area normalized reaction rate significantly improved for the ceramics exposed to electric field, until a maximum of three times for the material treated at 900 V/cm. Such enhanced properties were ascribed to the larger extent of Sr enrichment and in particular to the correlated field‐induced defect structure perturbation. Abstract : Strontium titanate nanoparticles prepared by hydrothermal synthesis were exposed to conventional and electric field assisted consolidation under air. Application of an electric field reduced grain growth and resulted in an enhanced segregation of strontium to the surface. The modification of the surface chemistry of the materials engendered significant improvement of the catalytic full oxidation of methane with respect to the conventionally treated counterpart